Toward Modern Classification of Eustigmatophytes, Including the Description of Neomonodaceae Fam. Nov. and Three New Genera1 - Amaral, Raquel; Fawley, Karen P; Němcová, Yvonne; Ševčíková, Tereza; Lukešová, Alena; Fawley, Marvin W; Santos, Lília M A; Eliáš, Marek (Journal of phycology, 2020)
The class Eustigmatophyceae includes mostly coccoid, freshwater algae, although some genera are common in terrestrial habitats and two are primarily marine. The formal classification of the class, developed decades ago, does not fit the diversity and phylogeny of the group as presently known and is in urgent need of revision. This study concerns a clade informally known as the Pseudellipsoidion group of the order Eustigmatales, which was initially known to comprise seven strains with oval to ellipsoidal cells, some bearing a stipe. We examined those strains as well as 10 new ones and obtained 18S rDNA and rbcL gene sequences. The results from phylogenetic analyses of the sequence data were integrated with morphological data of vegetative and motile cells. Monophyly of the Pseudellipsoidion group is supported in both 18S rDNA and rbcL trees. The group is formalized as the new family Neomonodaceae comprising, in addition to Pseudellipsoidion, three newly erected genera. By establishing Neomonodus gen. nov. (with type species Neomonodus ovalis comb. nov.), we finally resolve the intricate taxonomic history of a species originally described as Monodus ovalis and later moved to the genera Characiopsis and Pseudocharaciopsis. Characiopsiella gen. nov. (with the type species Characiopsiella minima comb. nov.) and Munda gen. nov. (with the type species Munda aquilonaris) are established to accommodate additional representatives of the polyphyletic genus Characiopsis. A morphological feature common to all examined Neomonodaceae is the absence of a pyrenoid in the chloroplasts, which discriminates them from other morphologically similar yet unrelated eustigmatophytes (including other Characiopsis-like species).
Keywords: Sequence Analysis, DNA; Pseudellipsoidion; Neomonodaceae; Chrysophyta; RNA, Ribosomal, 16S; Neomonodus; Phylogeny; ribozomální DNA; Chrysophyceae; Characiopsiella; sekvenční analýza DNA; Munda; DNA, Ribosomal; Eustigmatophyceae; fylogeneze; pyrenoid; RNA ribozomální 16S